Study on the Behavior of Helmholtz Resonance in Different Size Bottles - Adhikari, S.K.; Sapkota, B.; Dhungana, S.; Pokharel, P. (BMC Journal of Scientific Research, 2021)
The resonance is the specific response of system which is capable to vibrate with certain frequency to an external force acting with the same frequency. When air is blown across the open mouth of different bottles then air vibrate in a neck at resonant frequency. In this study we consider 5-5 bottles of different five types bottles having different of length of neck, radius of port, cross-sectional area of port and same volume (250ml). Resonance in different bottles was studied to determine how the volume of air cavity of different bottle affects the resonance. From calculated and experimental data, we found that the Helmholtz resonance frequency decreases with increase in volume and vice versa in each case of different bottles. From graph we also found that the calculated and experimental model are about 100% and 99% variability of the response data around its mean. The practical range for these different bottles is from about 256 to 512 Hz. This is about an octave plus a musical fifth near the middle of the musical instrument, so most simple musical tunes can be produced with such bottles.